2016
DOI: 10.1167/tvst.5.6.13
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Pediatric Visual Field Test

Abstract: PurposeWe describe a pediatric visual field (VF) test based on a computer game where software and hardware combine to provide an enjoyable test experience.MethodsThe test software consists of a platform-based computer game presented to the central VF. A storyline was created around the game as was a structure surrounding the computer monitor to enhance patients' experience. The patient is asked to help the central character collect magic coins (stimuli). To collect these coins a series of obstacles need to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…We were able to recruit 21 children with established pathology where visual field changes might be expected and all children completed the test satisfactorily. Median age was 12 (range, [4][5][6][7][8][9][10][11][12][13][14][15][16]. Thirteen children had congenital glaucoma, seven had secondary glaucoma, and one had neurological damage to a temporal lobe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to recruit 21 children with established pathology where visual field changes might be expected and all children completed the test satisfactorily. Median age was 12 (range, [4][5][6][7][8][9][10][11][12][13][14][15][16]. Thirteen children had congenital glaucoma, seven had secondary glaucoma, and one had neurological damage to a temporal lobe.…”
Section: Resultsmentioning
confidence: 99%
“…Further details including the development of the test hardware and software are given in previous publications. 8,9,12 We recorded details of consenting children and pertinent game data including visual field outcomes and reliability indices. One eye of each child was used for the study, determined by subject preference.…”
Section: Methodsmentioning
confidence: 99%
“…Such a perimetric procedure of permitting eye movements is increasingly explored both for adults and children. 2 , 28 However, the testing conditions for those equipments require the patient to be seated. We found the supine position in dark room testing to be encouraging for our patients with cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Even testing young children (age, ≥4 years) still remains a challenge. 1 , 2 Infants and children with neurological impairments (e.g., neonatal encephalopathies) are known to have visual field defects. 3 , 4 It has been reported that in otherwise healthy individuals, visual field defects arising during infancy gets detected only in adulthood.…”
mentioning
confidence: 99%
“…The Model of Health and Health Deficits has been applied by authors contextually to vision impairment (Berger and Porell, 2008;Crews et al, 2012); and as a framework for the outcomes of certain interventions (Neves et al, 2005).…”
Section: Colenbrander's Model Of Health and Health Deficitsmentioning
confidence: 99%